Strategi Meningkatkan Minat Baca Siswa SMA Ma’arif 1 Pamekasan Melalui Program Literasi - El-Haris, Fina Tamara; Abidin, Zeinal; Sa’diyah, Halimatus (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This study aims to determine the strategy in increasing the reading interest of Ma'arif 1 Pamekasan High School students through the literacy program. The research method used by the author is a qualitative descriptive approach. Data were collected through observation, interviews and documentation at SMA Ma'arif 1 Pamekasan. The sources consisted of the principal, the head of the library, and the students of SMA Ma'arif 1 Pamekasan using the interactive model data analysis technique. The results of this study show that the strategies implemented at SMA Ma'arif 1 Pamekasan include providing interesting reading sources, routine literacy activities, creating a comfortable reading environment, and evaluating literacy programs. Although the literacy program has improved students' reading interest, insight and academic achievement. However, there are still some challenges such as the lack of book collections and the low reading interest of some students. However, the school tries to offer interesting literacy programs and collaborates with several stakeholders to improve library facilities. Overall, the literacy program at SMA Ma'arif 1 Pamekasan succeeded in increasing students' interest in reading, improving students' morale and making the learning environment more active and dynamic.